The Function of Charter-Myths and Trickster-Tales in Ethiopia - Molvaer, Reidulf K. (Aethiopica, 2004)
Where there is no consensus between rulers and ruled about the extent of and limits to the use of power, rulers usually invent charters that give them divine rights to wield power at their own discretion. Most people are law-abiding citizens even under such conditions, but their sympathies lie with the few who dare to take the law into their own hands and free themselves from the constraints imposed by society as if social rules were inviolable. Such people are a law unto themselves, just like rulers who consider themselves to be above the law, but on a much smaller scale. Without checks on behaviour ‘from above’, lawlessness would flourish; but trickster-tales may hint that obedience to the law is not absolute, and that rebellion is a possibility if power is misused. Trickster-tales remind rulers to be moderate in their use of power. ATTENTION: Due to copy-right no online publication is provided.